Effects of Kinesio® taping on skeletal muscle strength—A meta-analysis of current evidence - Csapo, Robert; Alegre, Luis M. (Journal of science and medicine in sport, 2015)
The purpose of this study was to test whether certain applications of Kinesio tapes might facilitate contraction and increase muscle strength in healthy adults. A meta-analysis of studies investigating the efficacy of Kinesio tapes application was performed. The scientific databases Pubmed and Google Scholar were systematically searched for appropriate articles. Descriptive statistics were extracted to calculate measures of effect size (Pearson's r) and estimate the overall population effect. The methodological quality of the included studies was assessed using a specific quality appraisal tool. In addition, the included studies were grouped according to the muscle groups examined, to test whether Kinesio tapes effects were dependent on the area of application. A total of 19 studies, comprising data of 530 subjects and 48 pairwise comparisons of muscle strength were included. The methodological quality of these studies ranged from moderate to good. While substantial variability of individual effect sizes was observed, the overall population effect (r=0.05, CI: −0.23 to 0.34) suggests that, on average, the potential to increase strength by application of Kinesio tapes is negligible. Comparisons between studies grouped by the muscle groups examined showed that the effects of Kinesio tapes are not muscle-group dependent. While the application of Kinesio tapes may have some therapeutic benefits, the usage of these tapes does not promote strength gains in healthy adults.